Whole genome sequencing data of Leptospira weilii and Leptospira kirschneri isolated from human subjects of Sri Lanka - Senavirathna, Indika; Jayasundara, Dinesha; Warnasekara, Janith; Matthias, Michael A.; Vinetz, Joseph M.; Agampodi, Suneth (Data in brief, 2024)
Leptospirosis is a re-emerging zoonotic disease. This article reports the complete genome sequences of three novel strains of Genus Leptospira: two from the species Leptospira weilii (FMAS_RT1, FMAS_PD2) and one from Leptospira kirschneri (FMAS_PN5). These isolates were recovered from the blood samples of acute febrile patients in different geographical and climatic zones of Sri Lanka. High-quality genomic DNA was extracted from the three isolates in mid-log phase cultures. Whole genome sequencing was conducted using the PacBio Single Molecule Real-Time (SMRT) platform to identify the species, genome features, and novelty of the strains. The annotation was conducted using RAST (Rapid Annotation Using Subsystem Technology version 2.0) and the NCBI Prokaryotic Genome Annotation Pipeline. The genome sequences of three isolates have been deposited in the Mendeley data repository and the National Center for Biotechnology Information (NCBI) repository. This data will be useful for future researchers when conducting comparative genomic analysis, revealing the exact mechanism of pathogenesis of leptospirosis and developing molecular diagnostic tools for early detection.